2015
DOI: 10.1103/physrevlett.114.157701
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Band Solar Cell with Extreme Broadband Spectrum Quantum Efficiency

Abstract: We report, for the first time, about an intermediate band solar cell implemented with InAs/AlGaAs quantum dots whose photoresponse expands from 250 to ∼6000 nm. To our knowledge, this is the broadest quantum efficiency reported to date for a solar cell and demonstrates that the intermediate band solar cell is capable of producing photocurrent when illuminated with photons whose energy equals the energy of the lowest band gap. We show experimental evidence indicating that this result is in agreement with the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Hence, for the case of the IBSC, the absorption of two below bandgap energy photons to create one electronhole pair has been demonstrated, for example, in several implementations that use III-V semiconductor quantum dots [11][12][13][14][15]. In addition, it has also been proved that the presence of the intermediate band does not limit the output voltage of the cell [16,17].…”
Section: Brief Review Of the Status Of Empirical Research On Novel Comentioning
confidence: 98%
“…Hence, for the case of the IBSC, the absorption of two below bandgap energy photons to create one electronhole pair has been demonstrated, for example, in several implementations that use III-V semiconductor quantum dots [11][12][13][14][15]. In addition, it has also been proved that the presence of the intermediate band does not limit the output voltage of the cell [16,17].…”
Section: Brief Review Of the Status Of Empirical Research On Novel Comentioning
confidence: 98%
“…42 Based on this model, Δ opt depends linearly on the fluence of 0.8-eV photons because the addition of an optical escape pathway reduces the mean time carriers spent in traps in either the QD or wetting layer and, therefore, increases the conductivity (therefore, the photocurrent) even for a fixed number of carriers. 30 It is worthwhile to mention here that in a recent work, Asahi et al 45 have reported a saturation of two-step photocurrents. However, unlike the work reported here involving the two-step photoexcitation from valence band to intermediate states and from intermediate states to conduction band, Asahi et al 45 observed the saturation by tuning "two-step" photoexcitation from valance band to conduction band and from intermediate states to conduction band.…”
Section: Carrier Escape Nature and Electric Field Effectmentioning
confidence: 99%
“…30,32,34,37,47 Under the ideal case, the device is assumed to be defect-free; therefore, the SRH or NR recombination will be completely eliminated. As discussed in Sec.…”
Section: 4248mentioning
confidence: 99%
“…1,3 Thus, the proposed implementation of QD-IBSCs must accompany an efficient two-step carrier generation via IB states, however, it has been a challenge to notably demonstrate this operation principle particularly at room temperature, 5 which is owed to a relatively small optical generation rate from the QD-IB states to CB. The rate of thermal escape of electrons from IB to CB continuum as well as recombination from CB to IB transitions (reverse process) increases significantly with increasing temperature, [6][7][8] and these processes inevitably lead to a drop in the open-circuit voltage V OC and eventually outweigh the current gained by QD absorption.…”
Section: Introductionmentioning
confidence: 99%